Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. - COLLADA, C; Jimenez, P; Gil, L (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.
Keywords: chloroplast DNA; differentiation; geographic distribution; Haplotypes; phylogeny; Quercus

SEED STORAGE PROTEINS IN FAGACEAE - SIMILARITY BETWEEN CASTANEA GLOBULINS AND QUERCUS GLUTELINS - COLLADA, C; CABALLERO, R G; CASADO, R; ARAGONCILLO, C (PLANT SCIENCE, 1991)
Castanea sativa Mill. and C. crenata Lieb. and Zucc. store 11S globulins as major seed proteins while Quercus ilex L. and Q. robur L., also members of the Fagaceae family, accumulate glutelins. The structure of the 11S Castanea globulins, which is similar to the accepted model for this class of proteins, has been studied by different two-dimensional electrophoretic methods. The oligomer has a M(r) of 240 000-260 000, and the pairs of acidic-basic subunits, which form it, show great heterogeneity. The Quercus glutelins are made up of dimers linked by disulphide bridges, and their characteristics indicate a similarity to the subunits of 11S Castanea globulins. We suggest that, as in the case of rice glutelins, Quercus glutelins can also be considered legumin-like proteins.
Keywords: 11S GLOBULINS; Castanea; GLUTELINS; Quercus